Pelatihan Pembukuan dan Pencatatan secara Akuntansi Digital kepada Karang Taruna di Kelurahan Maleer Kota Bandung - Dewi Pramanik, Nuniek; Nurdin, Jusuf; Hatimatunnisani, Hani; Basith Sukarno, Hasbi; Robiul Rochmawati, Dwi; Karyadi (LPPM Politeknik Piksi Ganesha, 2024)
The training on bookkeeping and digital accounting records is a form of community empowerment aimed at improving financial literacy and managerial skills, particularly among the youth of Karang Taruna in Maleer Village, Bandung City. This program seeks to introduce digital accounting technology as a practical and efficient solution for managing the finances of their organizations or small businesses. The training covers the fundamentals of accounting, the use of digital accounting applications, and practical exercises in recording transactions systematically and accurately. The results of the training showed an improvement in the participants' understanding and skills in managing digital bookkeeping, which had a positive impact on the financial management of their organizations. Furthermore, this training provided insights into the importance of good financial recordkeeping to support transparency and better decision-making. It is hoped that this program will contribute to the capacity building of Karang Taruna and promote economic self-reliance within the local community